2003
DOI: 10.1128/jcm.41.6.2633-2640.2003
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus DNA Is Consistently Detected in Lungs of Patients with Idiopathic Pulmonary Fibrosis

Abstract: On the basis of earlier reports associating Epstein-Barr Virus (EBV) with half of the cases of idiopathic pulmonary fibrosis (IPF), we hypothesized that chronic infection with EBV or a closely related herpesvirus would be detected in all cases of IPF. We tested lung specimens from 33 IPF patients (8 patients with familial IPF and 25 patients with sporadic IPF) and 25 patients with other diseases as controls for the presence of eight herpesviruses using PCR-based techniques. One or more of four herpesviruses (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
250
1
13

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(270 citation statements)
references
References 33 publications
6
250
1
13
Order By: Relevance
“…Whilst EBV has been the most frequently studied of the HHVs, TANG et al [18] looked more broadly at a range of HHV family members and found evidence of past infection with at least one HHV in 97% of patients with IPF compared to only 36% of healthy controls. Over 50% of the IPF patients in their study had evidence of past infection with at least two HHVs.…”
Section: Virusmentioning
confidence: 99%
“…Whilst EBV has been the most frequently studied of the HHVs, TANG et al [18] looked more broadly at a range of HHV family members and found evidence of past infection with at least one HHV in 97% of patients with IPF compared to only 36% of healthy controls. Over 50% of the IPF patients in their study had evidence of past infection with at least two HHVs.…”
Section: Virusmentioning
confidence: 99%
“…This suggests an exacerbated response to respiratory illnesses among patients with a cytokine polarization away from a type 1 response (23). In the context of chronic interstitial disease, data from a number of studies provide evidence that products from DNA viruses (cytomegalovirus, Epstein-Barr virus, and herpesvirus) are associated with lung tissue recovered from a significant number of patients with chronic pulmonary disease (13,14). Although there is yet only correlative information regarding a type 2 cytokine environment and recoverable viral components from these clinical specimens, it is of interest to speculate that there may be a causeand-effect relationship between these two findings.…”
Section: Cytokine Polarization and The Exacerbation Of Pulmonary Viramentioning
confidence: 99%
“…This virus is closely related to human Epstein-Barr virus and Kaposi's sarcoma-associated herpesvirus (human herpesvirus 8), two DNA viruses that have been associated with lung tissue recovered from patients with interstitial pulmonary fibrosis (13,14). Wild-type mice infected via the respiratory route with MuHV-68 exhibited a lytic infection of alveolar epithelial cells with a subsequent latent infection of B cells and an elevation of CD8 1 T cells (24).…”
Section: Experimental Models With An Altered Cytokine Phenotype Exhibmentioning
confidence: 99%
See 2 more Smart Citations